The Idiom of Love and Sacrifice: Emotional Vocabularies of Motherhood in Nineteenth-Century Greece. (27th May 2017) - Vassiliadou, Dimitra
Abstract: In this article, I draw on a rich body of family correspondence from the second half of the nineteenth century in Greece. I perceive letters in correspondences as textual and material in-between places, and therefore as key sites for the creation and negotiation of maternal feelings. Switching constantly between small-scale autobiographical accounts and contemporary cultural perceptions of good motherhood, I argue that maternal love, the most crucial term of the emotional vocabulary at the time, overlaps with feelings and practices of self-sacrifice and suffering. Paradoxically, the rhetoric of selflessness, as a strong indication of a life-long maternal offering to children, requires specific obligations as a way of repayment. In researching the genealogy of maternal love, sacrifice and selflessness, the article shows the clear proximity of these notions to the wordings of Christian indoctrination and moral teaching of the period.